Effect of Work Motivation and the Work Environment on Performance Employees PT. Pos Indonesia (Persero) of Cirebon City - Deny Sudrajat; Dewi Dahlia; Edy Hartono; Japar Sodiq (Quantitative Economics and Management Studies, 2022)
This study aims to determine the effect of work motivation and work environment on employee performance at PT. Pos Indonesia (Persero) Cirebon City, the method used in this study is a quantitative method. The population in this study were employees of PT. Pos Indonesia (Persero) Cirebon City. The technique used in sampling is saturated sample, where the total population is used as a sample of 70 respondents. The method of collecting data is using a questionnaire, while the method in this study uses multiple linear regression. The results of this study indicate that work motivation has an effect on employee performance as seen from tcount > ttable , namely 5.341 > 1.99457. The work environment has an effect on employee performance as seen from tcount > ttable which is 6.097 > 1.9945 and simultaneously the variables of the influence of work motivation and work environment have a significant effect on employee performance calculated from Fcount > Ftable which is 57,472 > 3.13. From the partial results, work motivation has a sig value of 0.000 and the work environment has a sig value of 0.000 and the simultaneous results have a sig <0.05 or 0.000 <0.05.